2019
DOI: 10.4103/ijpvm.ijpvm_80_18
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between antioxidant status and attention deficit hyperactivity disorder among children

Abstract: Background: Attention deficit hyperactivity disorder (ADHD) is one of the prevalent neuropsychiatric disorders in childhood. In general, diagnoses of ADHD include inattention, hyperactivity, and impulsivity. Recent studies have reported increased oxidative stress in psychiatric disorders such as ADHD, but the results are conflicting. This research aimed to study the relationship between antioxidant status and ADHD in children of 6–13 years old. Methods: From schools, 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…MDA is the degradation product of the main chain reactions that lead to the oxidation of polyunsaturated fatty acids, and therefore serves as an oxidative stress marker. Recently, it was reported that the total antioxidant capacity, catalase and GSH were significantly lower but that MDA was not significantly different in children with ADHD [114]. However, high levels of MDA have been observed in both adults [115,116] and children with ADHD [117], and increased plasma MDA and urinary 8-OHdG levels were found in children with ADHD compared to healthy children [118].…”
Section: Oxidative Stress and The Relationship With Adhdmentioning
confidence: 99%
“…MDA is the degradation product of the main chain reactions that lead to the oxidation of polyunsaturated fatty acids, and therefore serves as an oxidative stress marker. Recently, it was reported that the total antioxidant capacity, catalase and GSH were significantly lower but that MDA was not significantly different in children with ADHD [114]. However, high levels of MDA have been observed in both adults [115,116] and children with ADHD [117], and increased plasma MDA and urinary 8-OHdG levels were found in children with ADHD compared to healthy children [118].…”
Section: Oxidative Stress and The Relationship With Adhdmentioning
confidence: 99%
“…It is noteworthy that another study identified high MDA concentrations in children with ADHD, but this difference lost statistical significance after corrections were applied [62]. Two included studies did not find significant differences in MDA levels [52,58]. However, Avcil et al noted in their study that measuring absolute values of various oxidative stress markers is often insufficient, suggesting the utility of calculating ratios between them.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Nasim et al . [ 37 ] detected low serum CAT, glutathione (GSH), and TAS levels in patients with ADHD.…”
Section: Discussionmentioning
confidence: 99%